Cardiovasculer Emergency Nursing: A Case Report - Diana Maidhotul Khasanah; Ning Arti Wulandari; Wimar Anugrah Romadhon; Maximiano Oqui (Health Gate, 2026)
Cardiovascular emergencies are diseases caused by heart and blood vessel failure. The cardiovascular system is a vital system in the human body. Therefore, diseases affecting this system can directly affect a person's survival. Researchers found several complaints, including shortness of breath, weakness, chest pain, and fatigue. Overlying diagnoses for patients with cardiovascular emergencies included decreased cardiac output, ineffective breathing patterns, and acute pain. Interventions for patients with cardiovascular emergencies were tailored to the diagnosis of bleeding. Evaluation of patients with cardiovascular emergencies was conducted for approximately 6 hours in the Emergency Department to determine the underlying issues. Most problems were unresolved and required further treatment, including hospitalization.